223k views
2 votes
Which best proves why the expressions 4 (x + 3) + 2 x and 6 (x + 2) must be equivalent expressions?

1 Answer

2 votes

Answer:

4(x + 3) + 2x and 6(x + 2) are equivalent

Explanation:

The best prove why two expressions must be equivalent is,

1. Simplify each expression to its simplest form

2. Show that the simplest form of them are equal

Let us do that with the given expressions

∵ The 1st expression is 4(x + 3) + 2x

→ At first, multiply the bracket (x + 3) by 4

∵ 4(x + 3) = 4(x) + 4(3) = 4x + 12

∴ The 1st expression = 4x + 12 + 2x

→ Add the like terms

∴ 4x + 12 + 2x = (4x + 2x) + 12 = 6x + 12

∴ The 1st expression = 6x + 12

The simplest form of the 1st expression is 6x + 12

∵ The 2nd expression is 6(x + 2)

→ Multiply the bracket (x + 2) by 6

∵ 6(x + 2) = 6(x) + 6(2) = 6x + 12

∴ The 2nd expression = 6x + 12

The simplest form of the 2nd expression is 6x + 12

∵ 6x + 12 = 6x + 12

∴ The simplest form of the two expressions are equal

∴ The expressions are equivalent

4(x + 3) + 2x and 6(x + 2) are equivalent

User Aditya Patawari
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.